2019
DOI: 10.1111/add.14792
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the commodity purchase task to evaluate behavioral economic demand for illicit substances: a review and meta‐analysis

Abstract: Background andAims The commodity purchase task is a simulated demand procedure that is easy and quick to complete (< 5 minutes) as well as adaptable for remote delivery and use with varied study populations. The purpose of this meta‐analysis was to synthesize research using the commodity purchase task with illicit substances to evaluate the magnitude of omnibus effects sizes and moderators of the correlation of demand indices with quantity–frequency (QF) and severity measures. Design Random‐effects meta‐analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 75 publications
4
57
1
Order By: Relevance
“…Using this methodology, evidence robustly supports relations between simulated demand assessments and concurrent and prospective prediction of real-world public health behaviors (8,14,18). However, limitations of the current study include non-probability sampling and assessment of intentions and selfreported histories, rather than actual vaccinations; note, however, prior evidence has shown a correspondence between seasonal influenza vaccination and pandemic influenza vaccination (32).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Using this methodology, evidence robustly supports relations between simulated demand assessments and concurrent and prospective prediction of real-world public health behaviors (8,14,18). However, limitations of the current study include non-probability sampling and assessment of intentions and selfreported histories, rather than actual vaccinations; note, however, prior evidence has shown a correspondence between seasonal influenza vaccination and pandemic influenza vaccination (32).…”
Section: Discussionsupporting
confidence: 53%
“…Purchase tasks require respondents to report their willingness to obtain a commodity at different prices, level of effort, or some other qualifying trade-off, and can provide a snapshot of consumption intentions under different market conditions. Such hypothetical purchase tasks simulate demand and significantly relate to or predict actual consumption (12,13) or clinical measures associated with substance consumption (14,15). Although such hypothetical tasks will never substitute for real, observed consumption, existing research suggests these are useful proxies when assessment of real-world behavior or other direct observation is impractical (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis on the concurrent validity of illicit purchase tasks has shown that sex and number of prices used are significant moderators of the relationship between P max , breakpoint and quantity and severity measures. 15 Also, consistent with the evidence of sex differences in alcohol use and related problems, 16 17 some studies have reported sex differences in demand, 18 19 but with divergent results on both the significance and the directionality of associations between APT indicators, making the results tentative so far. Combining individual APT studies allow meta-analysing potential moderators in a more cost-effective and powerful approach than any single study could do.…”
Section: Open Accessmentioning
confidence: 87%
“…Strickland et al . extend this literature with their timely and rigorous meta‐analytical summary of the smaller but growing body of literature examining illicit drug purchase tasks. A relative challenge with drug purchase tasks is the lack of standardization of drug doses and varieties compared to alcohol standard drinks.…”
mentioning
confidence: 98%